The Diversity of Understory (Shrubs And Herbs) in Mount of Nglanggeran - Akbar, Didik Zulfahmi; Widodo, Widodo; Agustina, Tanti (Proceeding International Conference on Science and Engineering, 2019)
Mount of Nglanggeran is areas that have diversity of unique flora. This area is uninhabited, so many diversity flora that not identified and have not experienced exploration. Therefore, further exploration of plant diversity is needed. The research is aim to inventory, documentation, and find out the diversity of understory (shrubs and herbs) on Mount Nglanggeran. This research used survey and exploration methods. The researchers documented shrubs and herbs species. Based on result, found 44 family consist of 144 species shrubs and herbs. Those species are flora that has specifically characteristics.